2012
DOI: 10.3892/or.2012.2194
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of adenovirus- and lentivirus-mediated expression of Drosophila melanogaster deoxyribonucleoside kinase on Bcap37 breast cancer cells

Abstract: Gene transfer using different viral vectors has demonstrated different antitumor effects in suicide gene therapy. In the present study, in order to optimize the efficacy of replication-defective adenoviral and lentiviral vectors for gene therapy, RT-PCR was used to evaluate the expression of Drosophila melanogaster deoxyribonucleoside kinase (Dm-dNK) in the Bcap37 human breast cancer cell line, dThd was used to determine the activity of Dm-dNK, cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The truncated variant A significant increase in the sensitivity of transfected cell lines to gemcitabine was observed, as shown by a decrease in IC 50 compared with control group. The IC 50 and folds of higher than previously reported for human uterine sarcoma cell line Messa 10K, where a full-length DmdNK was transfected to sensitize human cancer cell lines to various nucleosides [9,[41][42][43][50][51][52]. A possible explanation for the increased sensitivity to gemcitabine is the lower K m value of DmdNKΔC20 for this analog and unique interaction of fluoride atoms of gemcitabine [40].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The truncated variant A significant increase in the sensitivity of transfected cell lines to gemcitabine was observed, as shown by a decrease in IC 50 compared with control group. The IC 50 and folds of higher than previously reported for human uterine sarcoma cell line Messa 10K, where a full-length DmdNK was transfected to sensitize human cancer cell lines to various nucleosides [9,[41][42][43][50][51][52]. A possible explanation for the increased sensitivity to gemcitabine is the lower K m value of DmdNKΔC20 for this analog and unique interaction of fluoride atoms of gemcitabine [40].…”
Section: Discussionmentioning
confidence: 76%
“…DmdNK and its improved variants, produced by site-directed mutagenesis, have been tested for their optimum application in suicide gene therapy [38][39][40]. Both viral (adeno-and lentivirus-based vectors) and non-viral delivery systems have been used for transfecting different cancer cells with DmdNK and its mutants, to study the combined cytotoxic effect of gene/prodrug and to reverse drug resistance in various cancer cell lines [9,[41][42][43]. To the best of our knowledge, DmdNKΔC20 has not been reported neither for sensitizing human cancer cell lines to gemcitabine nor for the reversal of gemcitabine resistance in drug-resistant cancer cells so far.…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that expression of a single transgene is unlikely to be sufficient to eradicate cancer. Numerous studies have demonstrated that HSV-tk combined with cytokine therapy for the treatment of breast carcinoma had a high efficacy (18)(19)(20)(21). It has been shown that specific expression of CD or HSV-tk genes in breast as well as other cancer cells can be achieved using a vector delivery system containing VEGF promoter sequences (22).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the lentiviral vector has been identified to facilitate the incorporation of target genes into the host genome for efficient and stable expression of target genes in dividing and non-dividing cells (11,12). In the present study, a lentivirus vector was used to express the Dm-dNK suicide gene in keloid fibroblasts (KF).…”
Section: Introductionmentioning
confidence: 99%